2010
DOI: 10.1039/b924890k
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of atmospheric relevance: H2O/HCl/HNO3. Prediction of IR & MW spectra

Abstract: Theoretical calculations at the B3LYP/aug-cc-pVQZ level are performed on ternary clusters of water, hydrogen chloride and nitric acid to predict their IR and MW spectra. The main IR spectral features and their changes in a set of 15 selected clusters are analyzed in terms of the different hydrogen bonding characteristics of the aggregates. The formation of these clusters in laboratory experiments and their possible identification based on their infrared and microwave spectral properties are discussed. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The FTIR spectrum of Ag‐PPy is similar to the pure PPy spectrum except band at 1383 cm −1 . This band is attributed to the N–O symmetric stretch which indicated that the Ag‐PPy was doped by NO3 …”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of Ag‐PPy is similar to the pure PPy spectrum except band at 1383 cm −1 . This band is attributed to the N–O symmetric stretch which indicated that the Ag‐PPy was doped by NO3 …”
Section: Resultsmentioning
confidence: 99%
“…Nitric acid donates a proton to H 2 O in Figure 4aÀe and g, for which the OÀH vibrational frequency is red shifted by 509, 492, 493, 583, 565, and 302 cm À1 . The red shift of the OÀH stretch for Figure 4a was found to be À573 cm À1 at the B3LYP level with the aug-cc-pVQZ basis set by G omez et al 34 McCurdy et al reported the shift of the OÀH stretch of HNO 3 to be 654 cm À1 for the HNO 3 3 3 3 (H 2 O) 2 cluster. 28 On the other hand, in Figure 4f and hÀm, HCl accepts a proton from HNO 3 with the OÀH vibrational frequency of these trimers red shifted by 231, 142, 139, 136, 116, 118, and 112 cm À1 , respectively.…”
Section: Hcl H 2 O Shown Inmentioning
confidence: 94%
“…[22][23][24] Go´mez et al 22 reported fifteen structures characterized by true minima located on the IPES, the NC1W-1 aggregate being the most stable one among them. These structures are especially suitable for studying proton transfer parameter variations in the smallest clusters.…”
Section: Description Of the Systemsmentioning
confidence: 99%
“…This fact was also found in previous papers studying ternary clusters. 22,23 Finally, the third factor involved in proton transfer in HNO 3 is related to the existence of a proton donor acting over the acidic oxygen atom, and also to which molecule that donor may be. For instance, proton transfer does not occur when the proton donor is water, as in NC4W-5 or NC4W-1, whereas in NC4W-4 a HCl donor on the acidic oxygen has a marked effect, making r PT become positive.…”
Section: Proton Transfermentioning
confidence: 99%
See 1 more Smart Citation